The effect of internalization and other psychologic factors on the remission and severity of wheeze in children. Issue 4 (13th April 2016) - Feitosa, Caroline A.; Santos, Darci N.; Barreto, Maurício L.; Rodrigues, Laura C.
Abstract: Background: Asthma prevalence in Latin America is high and continues to increase. There is evidence that the psychologic characteristics of the child are associated with greater asthma morbidity. This study aimed to investigate the independent effect of internalizing/externalizing problems on two asthma/wheeze outcomes: (i) remission and (ii) progression to severity on Latin American children with mild asthma symptoms at baseline. Methods: This was a prospective study in a cohort of 371 asthmatic children living in a poor urban area in Salvador, Brazil. The psychologic characteristics of the child were assessed using the Child Behavior Checklist (CBCL), and wheezing was defined using the ISAAC questionnaire at the start and end of follow‐up. A multiple logistic regression model with random effects was used to examine the association between the psychologic components and both outcomes. Results: Remission of symptoms of wheeze was observed among 229 (61.73%) children. Remission was 56% lower among children with internalizing problems (OR = 0.54, 95% CI 0.33–0.87, p = 0.01). In addition, we found that 19 (8.76%) of the children acquired severe symptoms during follow‐up and there was strong evidence of the effect of internalizing problems in increasing the risk of progression to severe wheeze symptoms (OR = 4.03, 95% CI 1.39–11.70, p = 0.01). Conclusions: Children with internalizing problems but not externalizing had less remission of wheezing, and a higher risk of acquiring severe symptoms. These results highlight the importance of psychologic care for children with asthma, to improve the prognosis of this condition.